Implementasi Penerapan Metode Pemberian Tugas untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas II SD Negeri 19 Mataram - S, Herry Indrayati (ANWARUL, 2022)
The goal to be achieved in this research is to find out the improvement of mathematics learning outcomes by implementing the application of the assignment method for Class II students at SD Negeri 19 Mataram in the 2020/2021 academic year. The subjects of this study were 17th graders of SD Negeri 19 Mataram, consisting of 11 female students and 6 male students. This research uses action research in two cycles consisting of four stages, namely: design, activity and observation, reflection. The results showed that the learning outcomes of students II at SD Negeri 19 Mataram in the 2021/2022 academic year, with the assignment method, could be improved with the final result of the study being the class average score in the initial conditions of 69.47 or classical completeness 58.82%, becoming 73. .53 or 70.59% classical completeness in the first cycle, increased to an average of 78.18 or 82.35% in the second cycle and increased to an average test of 87.71 or 100% in the third cycle. From the results of student observations showed that there was an increase in student activity which in the first cycle obtained a score of 19 or 67.86% to 21 or 75.00% in the second cycle and 25 or 89.29% in the third cycle. The increase in student activities in learning Mathematics is supported by increased teacher activities in maintaining and improving the learning atmosphere using the assignment method, this can be seen from the observations of teacher activities where in the first cycle a score of 25 or 69.44% was obtained, to 27 or 75, 00% in the second cycle and increased to 32 or 88.89% in the third cycle.